2010
DOI: 10.1002/jcp.22349
|View full text |Cite
|
Sign up to set email alerts
|

Polymerization of insulin‐like growth factor‐binding protein‐1 (IGFBP‐1) potentiates IGF‐I actions in placenta

Abstract: Insulin-like growth factor (IGF)-binding protein-1 (IGFBP-1), the main secretory protein of decidua that binds to IGFs and has been shown to inhibit or stimulate IGFs' bioactivities. Polymerization, one of the posttranslational modifications of IGFBP-1, has been shown to lead to loss of inhibiting effect of IGFBP-1 on IGF-I actions. The current studies were undertaken to elucidate the effects of steroid hormones on IGFBP-1 polymerization in trophoblast cell cultures. Placental tissues were obtained during lega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 32 publications
3
7
0
Order By: Relevance
“…152, 153, 154 Vitamin A also induces insulin secretion from islets via TG2, 155 and steroid hormone-induced TG2 facilitates the crosslinking of IGFBP1 and increases IGF-I actions. 156 As a controversial effect, inhibitors of TG2, such as monodansylcadaverine and glycine methylester, do not prevent insulin secretion induced by either cAMP or phorbol ester at basal levels (10 nM) of Ca 2+ ; however, these inhibitors prevent insulin secretion induced by Ca 2+ . 157 These data indicate that the transamidation activity of TG2 has a critical role in insulin secretion.…”
Section: Diabetesmentioning
confidence: 99%
“…152, 153, 154 Vitamin A also induces insulin secretion from islets via TG2, 155 and steroid hormone-induced TG2 facilitates the crosslinking of IGFBP1 and increases IGF-I actions. 156 As a controversial effect, inhibitors of TG2, such as monodansylcadaverine and glycine methylester, do not prevent insulin secretion induced by either cAMP or phorbol ester at basal levels (10 nM) of Ca 2+ ; however, these inhibitors prevent insulin secretion induced by Ca 2+ . 157 These data indicate that the transamidation activity of TG2 has a critical role in insulin secretion.…”
Section: Diabetesmentioning
confidence: 99%
“…IGFBP-1 was recently found to undergo TG2-mediated polymerization on the surface of trophoblast cells, leading to its deactivation, the disinhibition of IGF, and, ultimately, enhanced IGF-dependent trophoblast cell migration (Shibuya et al, 2011). These findings suggested that progesterone might facilitate TG2-induced polymerization of decidua-secreted IGFBP-1 and increase IGF actions at the feto-maternal interface, thereby stimulating trophoblast invasion of the maternal uterus.…”
Section: Roles Of Tg2 In Cellular Processesmentioning
confidence: 99%
“…Insulin‐like growth factor (IGF)‐binding protein‐1 (IGFBP1) and decidual prolactin (PRL) are known to be biochemical decidualization markers (Brosens et al, 2014; Tamura et al, 2018). IGFBP1 secretion in the endometrium is suggested to be induced by P 4 through the activation of IGFBP1 polymerization (Gao & Tseng, 1997; Shibuya, Sakai, Kabir‐Salmani, Wachi, & Iwashita, 2011). Similarly, the expressions of uterine PRL and PRL receptor correlate positively with P 4 and E 2 levels (do Amaral et al, 2015).…”
Section: Effect Of Bpa On Decidualization Markersmentioning
confidence: 99%